Predicting the Physiological Effect of Revascularization in Serially Diseased Coronary Arteries: Clinical Validation of a Novel CT Coronary Angiography–Based Technique. (February 2019) - Modi, Bhavik N.; Sankaran, Sethuraman; Kim, Hyun Jin; Ellis, Howard; Rogers, Campbell; Taylor, Charles A.; Rajani, Ronak; Perera, Divaka
Abstract : Background: Fractional flow reserve (FFR) is commonly used to assess the functional significance of coronary artery disease but is theoretically limited in evaluating individual stenoses in serially diseased vessels. We sought to characterize the accuracy of assessing individual stenoses in serial disease using invasive FFR pullback and the noninvasive equivalent, fractional flow reserve by computed tomography (FFRCT ). We subsequently describe and test the accuracy of a novel noninvasive FFRCT -derived percutaneous coronary intervention (PCI) planning tool (FFRCT-P ) in predicting the true significance of individual stenoses. Methods and Results: Patients with angiographic serial coronary artery disease scheduled for PCI were enrolled and underwent prospective coronary CT angiography with conventional FFRCT -derived post hoc for each vessel and stenosis (FFRCT ). Before PCI, the invasive hyperemic pressure-wire pullback was performed to derive the apparent FFR contribution of each stenosis (FFRpullback ). The true FFR attributable to individual lesions (FFRtrue ) was then measured following PCI of one of the lesions. The predictive accuracy of FFRpullback, FFRCT, and the novel technique (FFRCT-P ) was then assessed against FFRtrue . From the 24 patients undergoing the protocol, 19 vessels had post hoc FFRCT and FFRCT-P calculation. When assessing the distal effect of all lesions, FFRCT correlated moderately well with invasive FFR ( R =0.71; P <0.001). For lesion-specific assessment, there was significant underestimation of FFRtrue using FFRpullback (mean discrepancy, 0.06±0.05; P <0.001, representing a 42% error) and conventional trans-lesional FFRCT (0.05±0.06; P <0.001, 37% error). Using FFRCT-P, stenosis underestimation was significantly reduced to a 7% error (0.01±0.05; P <0.001). Conclusions: FFR pullback and conventional FFRCT significantly underestimate true stenosis contribution in serial coronary artery disease. A novel noninvasive FFRCT -based PCI planner tool more accurately predicts the true FFR contribution of each stenosis in serial coronary artery disease.